Characterization of antibiotic-producing bacteria from cassava tape fermented by traditional ragi tape - NURHAYANI H. MUHIDDIN; NETTY HERAWATI; RAMLAWATI RAMLAWATI; NURUL HIDAYAH (Society for Indonesian Biodiversity, 2024)
Abstract. Muhiddin NH, Herawati N, Ramlawati, Hidayah N. 2024. Characterization of antibiotic-producing bacteria from cassava tape fermented by traditional ragi tape. Biodiversitas 25: 3359-3368. This study was carried out to determine the phenotypic and molecular characteristics and identification of antibiotic producing bacterial isolates from cassava tape fermented by traditional ragi tape. The type of research is exploratory, including isolation and characterization of antibiotic-producing bacterial isolates from cassava tape fermented by traditional ragi tape from Bone District and Gowa District, South Sulawesi Province, and Polewali Mandar District, West Sulawesi Province. Bacterial isolation was done using the pour cup method, and an antibiotic test was performed using the Kirby-Bauer method with Escherichia coli and Staphylococcus aureus as indicator bacteria. The isolation process yielded two bacterial isolates that exhibited antibiotic properties, namely isolates Bb1 and Bb2. The phenotypic characterization of the isolate Bb1 revealed an irregular shape, bacillus-cell shape, Gram-positive, the presence of endospores, positive catalase, motile, aerobic, positive citrate, the capacity to ferment glucose, producing acid and acetyl methyl carbinol. Meanwhile, the Bb2 isolate exhibits a round colony shape, bacillus-cell shape, Gram-positive, produces endospores, positive catalase activity, motile, facultatively anaerobic, negative citrate, can ferment glucose and lactose, produces acid and acetyl methyl carbinol. The results of molecular identification demonstrated that bacterial isolate Bb1 exhibited a 99.72% homology level with Bacillus velezensis strain CR-502. In comparison, bacterial isolate Bb2 showed a 99.58% homology level with Bacillus paramycoides strains MCCC 1A04098. The findings indicate that bacterial isolates derived from cassava tape fermented by traditional ragi tape have the potential to be developed into functional foods and novel antibiotic compounds for application in the healthcare sector. This study highlights the importance of phenotypic and molecular characterization in explaining the diversity of microorganisms present in cassava tape as a traditional food fermentation.